Explorations in the Second Christian Century : Texts, Groups, Ideas, Voices - Lieu, Judith M. (Ancient Judaism and Early Christianity, 2025)
As allegiance to Jesus Christ spread across the Roman Empire in the second century, writings, practices, and ideas erupted in a creative maelstrom. Many of the patterns of practice and belief that later become normative emerged, in the midst of debate and argument with neighbours who shared or who rejected that allegiance. Authoritative texts, principles of argument, attitudes to received authority, the demands of allegiance in the face of opposition, identifying who belonged and who did not, all demanded attention. These essays explore those divergent voices, and the no-less diverse and lively debates they have inspired in recent scholarship.